A study of policy implementation strategy of the Shari’ah in Aceh Barat - Putri Maulina, Arfriani Maifizar, Triyanto,; Said, Kamaruddin M.; Muhammad, Zikri; Ma’mun, Sukron (Opción, 2019)
The aim of the study is to investigate the policy implementation strategy of the Shari’ah in Aceh Barat. The research method is qualitative with primary and secondary data collection. Data analysis is conducted with descriptive analysis and qualitative approach. The results of this research show the necessity of the development strategy of socialization to the community in the implementation of the qanun. Furthermore, education support and people understanding are also important to the implementation strategy well underway. In conclusion, the formation of rules for the offenders as well as non-Muslim and foreigners should be in the implementation strategy